Chemoenzymatic Synthesis and Facile Purification of Gangliosides. Issue 3 (24th March 2021) - Bai, Yuanyuan; Yu, Hai; Chen, Xi
Abstract: Gangliosides are biologically important sialic acid‐containing glycolipids found commonly in human and other vertebrates. Isolation of pure gangliosides from cells or tissues is difficult, and chemical synthesis of gangliosides usually involves numerous steps with low synthetic yields. We report here a chemoenzymatic synthesis and purification protocol for two ganglioside cancer antigens, GM3 and GD3. One‐pot multienzyme glycosylation reactions are used to sequentially prepare GM3 and GD3 sphingosines from chemically synthesized lactosyl sphingosine. A facile C18‐cartridge purification procedure after each glycosylation reaction provides the desired pure glycosyl sphingosine product, which is readily acylated to form the target ganglioside. © 2021 Wiley Periodicals LLC. Basic Protocol : Chemoenzymatic synthesis and purification of GM3 and GD3 gangliosides Support Protocol : Monitoring reactions by thin‐layer chromatography